DAMPAK PENGGANDA USAHA KECIL SEKTOR PARIWISATA TERHADAP PERTUMBUHAN PEREKONOMIAN BALI: SUATU PENDEKATAN MODEL INPUT-OUTPUT - MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Development in Bali Province Bali based on economic aspect with emphasis atagricultural sector in wide meaning to continue of efforts to settle self sufficiency in food,development of tourism sector with character culture of Bali which is soul by Hinduism, andalso small industrial sector and small industry which related to agricultural sector andtourism sector. Objective of the research area: (1) to know contribution of small industry ontourism sector to Bali regional income (gross added value), (2) to know know impact ofoutput and income multiplier generated by small industries at tourism sector toward growth ofeconomics sectors in Bali. This research use approach of Input-Output Tourism Bali year2000, as source of data and also data-processing method to answer the objective research.Result of research found that: (1) contribution of tourism small enterprise toward Baliregional income (gross added value) is equal to Rp 2.694.049 million or 16,3% fromtotalizing income of Bali regional. Primary Input Coefficient of torism small small enterpriseequal to 0,618 (> 0,5) including is efficient, because it can create wages, salary, profit orenterprise surplus and indirect tax that big, meaning also can become mover machine of Balieconomics region, specially indirect and direct society activities who related direct andindirect to the small industry mentioned; (2) The tourism small enterprise has outputmultiplier impact bigger than average multiplier. This indicates that small industries attourism sector have ability as trigger of growth of Bali region economics region. Althoughthis small industry have income multiplier impact smaller than average multiplier, but thissmall enterprise can create income higher toward other economic sectors from each of onesmonetary that expended to fulfill request finally.Tourism small enterprise have potential and strategic role to be developed and alsopersonate as trigger of economic growth. Therefore this tourism small enterprise should bedeveloped and constructed , either through capital aid, training of management, and also aidaccess market, so that powered progressively and professional.